2023
DOI: 10.1186/s40708-023-00192-w
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and detection of virtual reality induced cybersickness: a spiking neural network approach using spatiotemporal EEG brain data and heart rate variability

Abstract: Virtual Reality (VR) allows users to interact with 3D immersive environments and has the potential to be a key technology across many domain applications, including access to a future metaverse. Yet, consumer adoption of VR technology is limited by cybersickness (CS)—a debilitating sensation accompanied by a cluster of symptoms, including nausea, oculomotor issues and dizziness. A leading problem is the lack of automated objective tools to predict or detect CS in individuals, which can then be used for resista… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
1
0
Order By: Relevance
“…The researchers concluded that while various models for detecting cybersickness have been developed, there is no model to predict early adverse events in VEs. Future, more accurate and effective ML approaches will undoubtedly be inspired by current knowledge of how the brain works, as well as the new brain/organism models/approaches being developed and linking them to these bio-digital frontiers ( Benelli et al, 2023 ; Daşdemir, 2023 ; Yang et al, 2023 ). These and similar studies ( Chang et al, 2023 ; Souchet et al, 2023 ) indicate, as does our research, that we are still at the beginning of understanding the potentially beneficial and detrimental effects of digital worlds on their users, especially older adults ( Drazich et al, 2023 ; Séba et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The researchers concluded that while various models for detecting cybersickness have been developed, there is no model to predict early adverse events in VEs. Future, more accurate and effective ML approaches will undoubtedly be inspired by current knowledge of how the brain works, as well as the new brain/organism models/approaches being developed and linking them to these bio-digital frontiers ( Benelli et al, 2023 ; Daşdemir, 2023 ; Yang et al, 2023 ). These and similar studies ( Chang et al, 2023 ; Souchet et al, 2023 ) indicate, as does our research, that we are still at the beginning of understanding the potentially beneficial and detrimental effects of digital worlds on their users, especially older adults ( Drazich et al, 2023 ; Séba et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies (e.g., [31,32]) have explored innovative approaches in EEG analysis and machine learning, such as Convolutional Neural Network-Long Short-Term Memory (CNN-LSTM) and the Spiking Neural Network (SNN). While these methods offer valuable insights, they are particularly tailored to addressing specific methodological challenges, such as time series analysis and noise robustness.…”
Section: Discussionmentioning
confidence: 99%
“…The EEG data underwent several preprocessing steps, which were successfully implemented in previous studies (e.g., [3,8]). These steps included applying band-pass filtering (BPF) in the range of [1,32] Hz to capture the delta, theta, alpha, and beta frequency bands. These bands are crucial for the cognitive tasks under investigation and are less susceptible to high-frequency noise [21,22].…”
Section: Eeg Recordings and Data Pre-processingmentioning
confidence: 99%